Avaliação da função renal de citricultores expostos a agrotóxicos no munícipio de Boquim no estado de Sergipe - Prudente, Ivângela Raphaela Gouveia (2018)
Agriculture corresponds to one of the main food sources in the world and increasing productivity has led to the implementation of automated machines and the use of pesticides to combat crop pests. As a result of the indiscriminate use of these chemicals and also the unprotected exposure to them, various health damages to rural workers have been recorded. After contact with the organism, most of the pesticides are eliminated through the kidneys, making this organ susceptible to physiological changes. In view of the above, this study aimed to evaluate the renal function of citrus growers in the city of Boquim, in the state of Sergipe. A cross-sectional observational epidemiological study was carried out with 208 citrus growers in the city of Boquim. The study participants answered questionnaires whose data contributed to the collection of sociodemographic information for the evaluation of occupational and behavioral risks, as well as information about symptoms of renal changes. Blood samples were collected for evaluation of renal function markers and subsequent determination of the glomerular filtration rate. In addition, it was possible to measure butyrylcholinesterase (BChE) in order to determine the existence of organophosphate poisoning. To complement the findings, urine samples were still collected for proteinuria. The data were tabulated in Excel spreadsheets and submitted to statistical analysis using the Graphad Prism program. The results were considered significant with p <0.05. The sample consisted mainly of male farmers (78.8%), belonging to social classes D and E, illiterate and residing predominantly in rural areas. Regarding the occupational aspects, the majority were workers / employees, with more than 5 years in contact with pesticides, with low adherence to the use of personal protective equipment. The pesticides of the organophosphorus class were the most used among the participants. The most frequent suggestive clinical manifestations of renal function disorders were nocturia, fatigue, and dysuria. Through the evaluation of the glomerular filtration rate (GFR), it was observed that 35.1% of the workers presented GFR between 60.0-89.9 ml/min/1.73m2, classified as Stage 2 (mild Renal Insufficiency), 3.6% between 45.0 - 59.9 ml/min/1.73m2, classified as Stage 3a (mild to moderate Renal Failure) and 1.2% with GFR between 30.0 - 44.9ml/min/1.73m2, being classified as stage 3b (Moderate to Severe Renal Insufficiency). BChE activity was reduced by 4.1% of workers. It was also possible to verify the association between the age group and alterations in creatinine, BChE and GFR levels. In addition to social class and BChE, the time of the last contact with pesticides and proteinuria was also considered. In this study, it was possible to observe a positive correlation between creatinine and urea, proteinuria and urea, GFR and butyrylcholinesterase, and negative correlation for GFR and urea, and GFR and creatinine. Thus, the results obtained demonstrate the existence of an association between exposure to pesticides and alteration of renal function, indicating the risk to which these workers are exposed. Therefore, this study may contribute to the development of future public health strategies, intended to prevent aggravations in people exposed to agrochemicals.